Program Universal Health Coverage Jaminan Kesehatan Medan Berkah (UHC JKMB) Untuk Meningkatkan Pelayanan Kesehatan Masyarakat Kota Medan dari Prespektif Otonomi Daerah - Genia Salsabila; Februati Trimurni (Administratio, 2024)
Universal Health Coverage (UHC) is a program designed to ensure access to quality healthcare services without financial hardship for all people. In the context of regional autonomy, the Medan City government is responsible for managing the health sector according to local needs, including implementing an ID card-based health service program. This study aims to analyze the success rate of UHC implementation in Medan City by assessing four key indicators: human resources, financial capacity, equipment and supplies, and organization and management. The research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The study was conducted at the Medan City Health Office and involved various stakeholders, including community members. The results indicate that Medan City has met or exceeded targets across all four indicators. The budget allocation for UHC by the Medan City government surpassed the minimum requirement, positively impacting the availability of healthcare services by expanding access for the community. Additionally, health organizations and management demonstrated significant efficiency despite challenges in inter-agency coordination, as communication relied primarily on essential platforms like WhatsApp groups, needing a more integrated and real-time online information system. While financial commitment and resource management have supported the success of UHC, there still need to be more public awareness, as evidenced by the limited understanding of UHC among community members. These findings suggest that the success of UHC in Medan could be further enhanced by implementing an online information system to improve inter-organizational coordination and increase public awareness of the benefits of UHC.